NCL-Tester - Graphic Application for NCL Documents Temporal Test Creation - Barreto, Fábio; Batista, Daniel Tamaki; Santos, Joel André Ferreira dos; Muchaluat-Saade, Débora C. Muchaluat (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2016: Proceedings of the 22nd Brazilian Symposium on Multimedia and the Web, 2016)
Interactive digital TV applications with runtime errors would certainly damage the viewer's experience. Testing NCL multimedia applications is very important to ensure that they will run appropriately on a digital TV receiver and really fits the author's specification. In the literature, there are works that propose tools for checking consistency of NCL documents. However, most of these works do not provide a graphical editor that facilitates the specification of temporal tests that can be used to verify if a document executes as desired. This paper proposes a new graphical tool, called NCL-Tester, which offers such functionality for NCL documents. Through NCL-Tester, an NCL application designer can specify temporal relationships between its media components and test whether these relationships will be respected when the NCL application runs. NCL-Tester uses aNaa (API for NCL Authoring and Analysis) to run the tests and returns to the author a success or error message for each test. The usefulness of the proposed tool was verified by usability tests.